THE UNGRAMMATICAL CONSTRUCTIONS IN ENGLISH WRITING: ANALYSISONTYPES AND CAUSES - Cenderato, .; ., Sudarsono; Sutapa, Y, Y. Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The present research is about analysis on ungrammatical constructions encountered in the texts written by Senior High School students. The objective of the study is to describe the ungrammatical constructions in clauses and phrases. The method of research is descriptive. The research participants were 28 students of Year-XI of â€œSMAN 1 Nanga MerakaiSintangâ€ in Academic Year 2013/2014. The data were collected from corpus written by the students. The students were still weak at writing texts. The grammatical constructions were 19 (13.77%) and 119 (86.23%) not. The grammatical problems concern the phrasal and the clausal construction. That was 55.47% of the ungrammatical phrases have been made by the students. The other 44.53% ungrammatical constructions were at clauses.Â  There was 53% of interlingual problem made by the students. The errors were Omission of â€œto beâ€, Noun phrase and Preposition phrase and 47% of intralingual errors. Keywords: ungrammatical construction, Types, Causes Abstrak: Penelitian iniadalahtentang analisis pada konstruksi gramatikal yang dihadapi dalam teks. Tujuan dari penelitian ini adalah untuk menggambarkan konstruksi gramatikal dalam klausa dan frasa.Metode penelitian yang digunakan adalah deskriptif. Partisipandalam penelitian iniadalah 28 siswa dari tahun-XI SMAN 1 Nanga Merakai Sintang Tahun Ajaran 2013/2014. Data dikumpulkan dari corpus yang ditulis oleh siswa. Konstruksi gramatikal sebanyak19 (13,77%) dan sedangkan119 (86,23%)tidakgramatikal. Masalah tata bahasa terfokuspadaphrasadan penulisanklausa.Di tingkat phrasa, masalah tata bahasa berkaitan dengan urutan phrasa kepala dan pengubahnya. Sebanyak55,47% kesalahanditingkatfrasa. Sebanyak44.53% konstruksi gramatikal lainnya berada di klausa.misalnayapenghilangan "to be", kecocokanSubjekdan kata kerja dan penghilangan Subyek. Masalah-masalah tata bahasa disebabkan oleh pengaruhbahasaibu dan masalahkesulitandalambahasa yang dipelajari. Ada 53% masalah yang dihadapisiswadalammenulisadalahkarenapengaruhbahasaibu. Kesalahan penghilangan "be", frasabenda dan frasa Preposisi dan 47% dari kesalahan intralingualataubahasa yang dipelajari. Kata kunci: ingramatikal, KontruksidanKesalahan